Poverty in Albania A qualitative assessment - Herme De Soto; Soto, Hermine De; Gordon, Peter; World Bank technical paper; no. 520 (Washington, D.C.: World Bank, 2002)
This qualitative assessment o poverty in Albania seeks to deepen the understanding of poverty in the country by involving poor Albanians in a process of exploring the causes, nature, extent of poverty and how it affects their lives.
World Bank Technical Paper No. 520
Incudes bibliography
osa 16/08/16
Loans
Keywords: Poverty - Albania; Albania - economic conditions; Albania - economic history